Optimizing Operating Room Efficiency for Primary Hip and Knee Arthroplasty Using Performance Benchmarks - Koorosh Kashanian, BMSc; Matey Juric, BSc; Tim Ramsay, PhD; Pascal Fallavollita, PhD; Paul E. Beaulé, MD, FAAOS, FRCSC (Arthroplasty Today)
Background: With increasing demand for total hip arthroplasty (THA) and total knee arthroplasty (TKA), maximizing operating room (OR) efficiency is critical. This paper sought to examine the implementation of time benchmarks when performing primary TKA and THA. We hypothesized that implementing benchmarks would improve efficiency and the number of joints performed per day. Methods: Two hundred ninety-five patients from 59 OR days were reviewed. All surgeries were performed as outpatients and included 160 females and 135 males; 161 TKA and 134 THA; mean age, 66.1; mean body mass index, 28.6 kg/m2; American Society of Anesthesia, 2. Time points, demographics, and adverse events were recorded. Benchmarks to complete 4 joints in 8 h were: anesthesia preparation time (APT) of <11 min, procedure time of <72 min, anesthesia finish time (AFT) of <21 min, and turnover of <22 min. Results: The percentage of cases meeting individual benchmarks for APT was 50.17%; procedure time was 95.25%; AFT was 99.67%; turnover was 65.25%. The means were: APT 11:00 min, Surgical Prep Time 9:00 min, procedure time 55:00 min, AFT 3:00 min, and turnover 19:00 min. Overall, 98.3% (58/59) of ORs had 4 cases completed within 8 h and 52.5% (31/59) had 5 cases within 8 h. Age, body mass index, and consecutive laterality of surgery were determined to affect the likelihood of meeting benchmarks for case time, APT, and turnover. Conclusions: Establishing time benchmarks permitted the introduction of 5 joint days within an 8-h OR without increasing resource utilization. Factors that influence OR efficiency for high-volume primary hip and knee replacements were identified.